Putrescine Is an Intraspecies and Interkingdom Cell-Cell Communication Signal Modulating the Virulence of Dickeya zeae - Shi, Zurong; Wang, Qingwei; Li, Yasheng; Liang, Zhibing; Xu, Linghui; Zhou, Jianuan; Cui, Zining; Zhang, Lian-Hui (Frontiers in Microbiology, 2019)
The infections caused by Dickeya zeae become a severe problem in recent year, but the regulation mechanisms that govern the bacterial virulence remain to be fragmental. Here we report the investigation of potential involvement of polyamines in regulation of D. zeae virulence. We showed that null mutation of speA encoding arginine decarboxylase dramatically decreased swimming motility, swarming motility and biofilm formation, and exogenous addition of putrescine effectively rescues the defective phenotypes of D. zeae. HPLC and mass spectrometry analysis validated that SpeA was essential for production of putrescine in D. zeae. In addition, we demonstrated that D. zeae EC1 could detect and response to putrescine molecules produced by itself or from host plant through specific transporters. Among the two transporters characterized, the one represented by PotF played a dominated role over the other represented by PlaP in modulation of putrescine-dependent biological functions. Furthermore, we provided evidence that putrescine signal is critical for D. zeae EC1 bacterial invasion and virulence against rice seeds. Our data depict a novel function of putrescine signal in pathogen-host communication and in modulation of the virulence of an important plant bacterial pathogen.